The Effect of Employee Agility and Self-Efficacy on Innovative Behavior at Work - Dzimidienė, Agnė; Bagdžiūnienė, Dalia (Psichologija, 2022)
In order for organizations to remain competitive and successful in the contemporary business environment, one of the fundamental prerequisites is innovative behavior of employes. Therefore, research analyzing the organizational and personal factors of this behavior is relevant, in which increasing attention is paid to the agility of employees. In general, agility can be described as a person’s ability to adapt quickly and efficiently to normal or new work situations, accept changes and respond appropriately to them. The study aimed to determine the relationship between employees agility, self-efficacy, and innovative behavior in the organization and to evaluate the mediating role of self-efficacy for the relations between agility and innovative behavior. The cross-sectional survey was conducted in the sample of 172 employees. 78% of them were women, the average age of the participants was 33.8 years. Scales measuring employee agility, innovative behavior and self-efficacy were applied in the study. For this study, a Lithuanian employee agility scale consisting of twenty items was prepared. The results were processed using correlational, regression, and mediation analysis. Main results: firstly, more expressed employee agility and self-efficacy predicts their higher involvement in innovative behavior, and secondly, self-efficacy acts as a mediator for the relationship between agility and innovative behavior. The importance of the employee’s personal characteristics – agility and self-efficacy – in predicting innovative behavior was confirmed, and the role of self-efficacy as a mediator for the relationship between agility and innovative behavior was revealed. Theoretical and practical implications of the study results are discussed.
Keywords: employees; innovative behavior; agility; self-efficacy